Away - Freeman, Megan E. (New York : Aladdin, 2025)
Told from multiple points of view, this novel follows four kids relocated to the same evacuation camp who investigate the mysterious threat that forced the large-scale exodus. Told in verse format.
Ages 12 and up.
Grades 7-9.
Keywords: Evacuation of civilians -- Juvenile fiction; Dystopias -- Juvenile fiction; Conspiracies -- Juvenile fiction; Dystopias -- Fiction; Conspiracies -- Fiction; Colorado -- Fiction; Colorado -- Fiction; Novels in verse; Dystopian fiction